The Assessment of Bone Metabolısm Parameters in Paedıatrıc patıents wıth Genu varum and Genu valgus deformıtıes - Kürüm, Hüseyin; Demir, Sukru; Key, Sefa (My University, 2024)
Aim: There are a limited number of studies in the literature explaining the relationship between bone metabolism parameters such as vitamin D, calcium (Ca), parathormone (PTH), magnesium (Mg), and alkaline phosphatase (ALP) and pediatric lower extremity coronal plane deformities.This study aimed to examine the impact of bone metabolism parameters on the development of genu varum or genu valgus deformities. Methods: 45 patients with genu varum and genu valgus whose vitamin D, Ca, PTH, Mg and ALP parameters were evaluated in our polyclinic were included in the study. Results: 44 (97.8%) of the patients were bilateral and one (2.2%) was unilateral. The mean age of patients with genu varum (4.3±4.8) was significantly lower than that of patients with genu valgus (11.9±4.1) (p<0.001). Ca values were normal in 44 (97.8%), vitamin D in 23 (51.1%), PTH in 33 (73.3%), ALP in 2 (4.4%) and Mg in 43 (95.6%) patients. 3% (6.7) of the patients had comorbidities. 2 of these (66.7%) were rickets. Conclusion: The study shows that ALP can be used as a screening test especially in the coming years. In addition, although there are no sufficient incidence and prevalence studies in the literature, we can say that genu varum is seen more frequently and mostly bilaterally than genu valgus.It is not uncommon for rickets to accompany lower extremity coronal deformities in children. In addition, McCune-Albright Syndrome (MAS) may be accompanied not only by fibrous dysplasia (FD) but also by bilateral genu valgum deformity.
Keywords: Genu varum; genu valgus; bone metabolism parameters